Drought alters plant-soil feedback effects on biomass allocation but not on plant performance - Wilschut, Rutger A.; van Kleunen, Mark (Plant and soil, 2021)
Aims Drought events can alter the composition of plant and soil communities, and are becoming increasingly common and severe due to climate change. However, how droughts affect plant-soil feedbacks is still poorly understood. Plants accumulate species-specific rhizosphere communities, and droughts may have varying impacts across plant species and soil biota. We therefore tested the hypothesis that drought alters plant-soil feedbacks differently among closely related plant species that differ in their preferences for soil moisture. Methods In a two-phase greenhouse experiment, we first conditioned grassland soil with seven Geranium species and, as controls, we conditioned soil with a grass species or left soil unplanted. In the second phase, we grew the Geranium species in conspecific, grass-conditioned and unplanted soil, maintained soil moisture at 5 %, 10 % or 20 % (w/w), and determined biomass responses after 35 days. Results Independent of conditioning, plants showed a weaker performance with decreasing soil moisture. Under the driest conditions, soil conditioning by conspecifics most negatively affected relative root weight in comparison to plants growing in unplanted control soil, while the effects of conspecific conditioning on relative root weights were species-specific when compared to plants grown in grass-conditioned control soil. Conclusions We conclude that decreased soil moisture modified plant-soil feedback effects on biomass allocation, and that these modifications acted in species-specific ways. However, drought effects on plant-soil feedbacks were subtle, and did not affect overall plant performance. Therefore, plant-soil feedback effects on plant performance during a drought event may be limited in comparison with the direct effects of drought.